Hepatic portal venous gas associated with colon cancer: A case report and literature review. Issue 50 (December 2017) - Li, Zhongmin; Su, Yanzhuo; Wang, Xueju; Yan, Hongbo; Sun, Mingze; Shu, Zhenbo
Abstract: Rationale: Hepatic portal venous gas (HPVG) is a very rare radiological finding that occurs when gas enters the portal venous system. HGVG can be caused by various diseases, with the most common being intestinal ischemia or necrosis. While there are few reports of HPVG associated with colon cancer, we report a case of HPVG associated with advanced colon cancer. Diagnosis: The diagnosis of this patient was HPVG caused by colon cancer. Interventions: Left colon cancer resection, pancreatic tail resection, splenectomy, and transverse colostomy were performed. Outcomes: The patient recovered well, and postoperative paraffin pathology confirmed that the resected tumor was colon cancer. Lessons: Abdominal computed tomography is an effective method for diagnosing and monitoring HPVG. Klebsiella pneumonia is a potential gas-producing microorganism associated with HPVG, which may be confirmed by Blood culture or drainage culture. The prognosis of HPVG is closely related to the underlying pathology. Surgery should be performed early when there are signs of intestinal ischemia, necrosis, or perforation.